Uneasy lies the head that wears a crown: How celebrity CEOs affect corporate social responsibility—An empirical study of Chinese listed firms - Mengxi Niu (Heliyon)
This study examines the influence of celebrity Chief Executive Officers (CEOs) on corporate social responsibility (CSR) in Chinese listed firms in the A-share market from 2009 to 2020. We employ a multi-theoretical approach, drawing on upper echelons, impression management, and identity theories to explore several aspects of this topic. We find that celebrity CEOs are associated with better CSR engagement, suggesting that celebrity CEOs are likely to utilize CSR to strategically manage their impressions. We then explore four boundary conditions in the relationship between celebrity CEOs and CSR, and how celebrity identity mechanisms moderate this relationship. We find that CEOs' age, gender, and degree of media attention can strengthen the celebrity CEOs–CSR relationship, explaining the boundary conditions influencing the level of celebrity CEOs' impression management motivation. Additionally, environmental dynamism does not influence the association between celebrity CEOs and CSR performance. Our study provides new insights into the understanding of CSR antecedents, particularly from the perspective of CEOs’ psychological motivation, and contributes to formulating future CEO and CSR strategies.